MEDIA DISCOURSE AND LINGUISTIC PLAY AS FEATURES OF POSTMODERN CONSCIOUSNESS (Uzbekistan Open Conference, 2025)
The article analyzes the language game as a fundamental principle of postmodern discourse, connected with its philosophical foundations in play. The author reveals the dual nature of play (free activity / activity governed by rules) and argues that in the context of the crisis of metanarratives, play becomes an adequate means of representing reality. Particular attention is paid to the functions of play: resistance to totalitarian systems, establishing a dialogue with the reader, and blurring the boundaries between the author and the recipient. Using examples from the works of Pelevin, Akunin, Ulitskaya, and Eco, the article demonstrates how game-texts create a space for co-creation, where a special “play mindset” becomes the main condition for communication.